Pembuatan Prototipe Tempat dan Aplikasi Pengembalian Koleksi Perpustakaan Secara Mandiri - A.B. Tjandrarini; Julianto Lemantara (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Library services of STIKOM Surabaya in returncollection is not optimal since the return time is limited to the business hours. The returning process also takes long time for barcode reading speed is longer than RFID and fines payment must be made directly at officer, causing queues for other members. This study aims to create prototype and collection return application that makes return process easier, faster, and more flexible in time and place. RFID tag was attached to acollection. The RFID reader located on the prototype was used to detect the collection return data. The data was checked at Library Information System to obtain borrowing status. If borrowing status is valid, then green light is on and if not valid, then red light is on. After the light turned green, the collectionreturn data was stored in the protype memory as backup.Besides, the return data was sent to the collection return application to be processed of return actual date, fines calculation, and time determination of rejected borrow. Experimental results show that the prototype of RFID reader equipped with a mechanism light has been successfully integrated with the collection return application module. The application can also perform the return process in changes ofreturn collection realization date, fines calculation, and time determination of rejected borrow.